The Effect of Extract Red Gingger (Zingiber Officinale Var. Rubrum) on Reducing the Blood Pressure Level among Maternal with Gestasional Hypertension - Naomi Christina Hutabarat; Supriyana Supriyana; Suhartono Suhartono (International Journal of Nursing and Health Services (IJNHS), 2020)
estational hypertension is a major cause of maternal and infant morbidity and mortality. Handling of hypertension is done by pharmacological therapy but provides side effects Red ginger can be used as one of the herbal therapies to reduce blood pressure. The main compound in red ginger can reduce cholesterol, reduce fat deposits in blood vessels and the risk of coronary heart disease. The study aimed to analyze the red ginger extract on reducing blood pressure level among maternal with gestational hypertension. A quasi-Experiment with pretest posttest design with equivalent control group design. Thirty-four patients were recruited and divided into experimental and control group Patients in the experimental group received the antihypertensive drugs plus red ginger extract at a dose of 500 mg for 14 days. While control group control group was given antihypertensive drugs with placebo. There was a significant difference in systolic blood pressure between the intervention and control groups with a value of p 0.000 and a diastolic p value of 0.000. In the intervention group there was a systolic decrease of 29.35 mmHg and a diastolic 16.00 mmHg. Red ginger extract has the potential to reduce systolic and diastolic blood pressure in women with gestational hypertension. Pregnant women with gestational hypertension can take advantage of red ginger extract as an alternative treatment for gestational hypertension. The next researcher can control psychological factors and check the levels of nitric oxide (NO) in blood / saliva